Are multiple coders needed for cause of death assignment: results from telephonic verbal autopsy interviews conducted in 2021 in South Africa - Neethling, Ian; Morof, Diane; Glass, Tracy; Kallis, Natasha; Rao, Chalapati; Bradshaw, Debbie; Groenewald, Pam (Digital health, 2024)
Introduction Verbal autopsy (VA) methods have emerged to estimate causes of death in populations lacking robust civil registration and vital statistics (CRVS) systems. Despite World Health Organization endorsement of routine VA use, cost and efficiency concerns persist. Telephonic verbal autopsies (teleVAs) can reduce cost. Physician coding offers a valuable approach, but the expertise required makes it resource-intensive, often involving multiple coders for consensus. Objective To assess inter-coder agreement for cause of death (CoD) in South African teleVAs using Kappa statistics, evaluating if agreement surpasses a 0.8 cut-off (very high) potentially allowing single coders. Methods A cross-sectional study employed telephonic VA interviews on non-facility deaths in Cape Town (December 2020–September 2021). Trained fieldworkers administered a standard VA questionnaire. Each case's VA responses were reviewed independently by two physicians, medically certifying the CoD. A panel was used to solve disagreements. Cohen’s kappa-statistic (k-statistic) tested agreement levels. Results Decedents were aged between 18 and 98 years. In total, 228 teleVAs (16.6% response rate) were conducted. Physician coding agreement was good overall (k-statistic: 0.63). Diabetes mellitus (47%) and other non-communicable disease (42%) had initial agreement between physician coders in less than 50% of cases in comparison to consensus totals. COVID-19 (89%) and acute cardiac disease (83%) showed initial agreement in more than 80% of cases compared to consensus totals. A chi-square test revealed a significant difference in the number of causes listed on death notification forms for cases with and without agreement in Part 1 (χ2 = 14.71, p < 0.01), but not in Part 2 (χ2 = 4.97, p = 0.17). Conclusion CoD agreement might not be high enough to infer that single coders can be used instead of multiple coders. Challenges with co-morbidities and specific CoDs with multiple sequelae highlight the need for further research and refinement of VA methodologies for reliable CoD determination in routine practice.